Colonization of Tomato Root by Antagonistic Bacterial Strains to Fusarium Wilt of Tomato - Arif Wibowo (Jurnal Perlindungan Tanaman Indonesia, 2005)
Fusarium wilt of tomato caused by Fusarium oxysporum f.sp. lycopersici (Fol) is an important disease in tomato which cause a significant loss of yield in major growing regions of the world. This study examined the ability of bacterial strains antagonistic to F. oxysporum f.sp. lycopersici (H5, H22, H63, H71, Burkholderia cepacia strain 65 and 526) to colonize tomato seedlings and the effect of plant growth. The effect of bacterial population size and air temperature on the bacterial colonization and their spread along the root systems was also assessed.The results of this study showed that the bacterial population at 28°/23° C day/night temperature 14 days after planting was significantly greater than 23°/18° C for 4 of 6 strains tested. Although there was no significant effect of temperature on bacterial population observed in this study, the ability of the baacterial strains to colonize the rhizosphere was significantly different. Three strains (H5, B. cepacia strain 65 and 526) survived well in the rhizosphere and at 4 weeks after planting rhizosphere populations per gram fresh root were not significantly different from those recovered 2 weeks after planting. The largest population of the bacterial inoculants developed in the basal region of the roots and this differed between strains by log10 2.7 cfu/cm root. The bacterial populations in other parts of the root were also strain dependent. Strain H71, for example, was able to colonize the root segments at a high population level. However strain H63 was recovered only in small number in all root segments.